(E-Reading) Electronic Reading: For Active and Interactive Learning Reading Based on Open-Source Software (OSS) - Herdina, Griselda Gian Heris; Fakhrurriana, Ria (Proceeding International Conference on Education, 2023)
Updates in technological innovation in the field of Education, especially English will be urgently needed. Technology in Education has revolutionized manual teaching and learning on an innovative, open-source basis. One of the innovations based on Open-Source Software (OSS) is Electronic Reading (E-Reading). It is designed for EFL class, especially in reading, so that it can run actively and innovatively based on a curriculum that will be packaged attractively and creatively so students can easily accept it. This study discusses based innovation between teaching reading and OSS sophistication compared to previous teaching techniques. This article limits how an OSS can make learning more conducive and productive. As a result, E-Reading strives to provide a beneficial experience for students in learning Reading with full features in the latest version and will be in accordance with the current English learning curriculum.